2014
DOI: 10.1111/eip.12159
|View full text |Cite
|
Sign up to set email alerts
|

Pathway model of parental help seeking for adolescents experiencing first‐episode psychosis

Abstract: Findings recommend intervention at three specific periods of help seeking. First, psychoeducation is needed when parents first engage with health care for their children's disabling conditions. Professionals treating childhood conditions need training to vigilantly monitor the overall mental health of the children over time. Second, it is important to enhance the roles of formal and informal community resources in facilitating parental help seeking. Finally, family-focused interventions are essential in suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 41 publications
1
32
0
1
Order By: Relevance
“…Linear regression analyses revealed that general mental‐health related stigma, and its sub‐factor of discrimination were significant predictors of DUP, even after adjusting for possible confounders. This is in line with the previous literature that has explored stigma and mental illness more broadly (Clement et al, ; Thornicroft, ) and qualitative papers that have observed this relationship in FEP (Anderson et al, ; Chen et al, ; Ferrari et al, ; Stewart, ). Discrimination in this study refers to the participant's perception of experiencing stigma, and may relate to lack of employment opportunities and negative reactions from others, including health professionals, family members and the criminal justice system.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Linear regression analyses revealed that general mental‐health related stigma, and its sub‐factor of discrimination were significant predictors of DUP, even after adjusting for possible confounders. This is in line with the previous literature that has explored stigma and mental illness more broadly (Clement et al, ; Thornicroft, ) and qualitative papers that have observed this relationship in FEP (Anderson et al, ; Chen et al, ; Ferrari et al, ; Stewart, ). Discrimination in this study refers to the participant's perception of experiencing stigma, and may relate to lack of employment opportunities and negative reactions from others, including health professionals, family members and the criminal justice system.…”
Section: Discussionsupporting
confidence: 90%
“…A small number of studies have assessed this relationship specifically in first-episode psychosis (FEP), with a substantial proportion of literature being qualitative (Anderson, Fuhrer, & Malla, 2013;Chen, Gearing, DeVylder, & Oh, 2014;Connor et al, 2016;Ferrari et al, 2015;Stewart, 2013;Welsh & Tiffin, 2012). A recent systematic review of mental-health stigma and pathways to care in FEP or at-risk populations revealed only nine quantitative articles with no study exploring the relationship between stigma and help-seeking from a patient perspective in FEP (Gronholm, Thornicroft, Laurens, & Evans-Lacko, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The final sample of CHR/FEP engagement studies consisted of 13 studies published between 2006 and 2015, all of which relied on qualitative methodology. Table provides more information about the methods of each study …”
Section: Methodsmentioning
confidence: 99%
“…Table 1 provides more information about the methods of each study. 12,13,[27][28][29][30][31][32][33][34][35][36][37][38] The second literature search targeted RCTs (i.e. 'CHR/FEP RCTs') evaluating psychosocial interventions, with or without pharmacotherapy, for CHR youth/young adults or youth/young adults with FEP.…”
Section: Literature Searchmentioning
confidence: 99%
“…Diese Auffälligkeit verdeutlicht, dass eine Psychoedukation helfen könnte, sich mit dieser Problematik zu beschäftigen, diesbezüglich Sorgen zu objektivieren und damit zu relativieren. Die Notwendigkeit einer Psychoedukation gerade bei erstmaligem Kontakt mit der Gesundheitsfürsorge betonten auch Chen et al [24]. Dass ein Mangel an Psychoedukation im stationären klinischen Alltag besteht, stellten Franz et al [9] heraus.…”
Section: Diskussionunclassified